The Influence of Motivation and Self-Efficacy on Normative Commitment of Teachers at SMK Negeri 4 Pontianak - Agustina, Andi Siska; Mahdi, Irfan (Jurnal Manajemen Bisnis, 2025)
This study examines the impact of Motivation and Self-Efficacy on the Normative Commitment of teachers at SMK Negeri 4 Pontianak, where absenteeism is a recurring issue. The absentee rate increased by 35.83% in 2021 and surged by 180% in 2022, before declining by 35.61% in 2023. The improvement in 2023 was partly due to teachers attending training and workshops outside West Kalimantan. However, disciplinary violations persist, including teachers leaving during working hours, harshly reprimanding students, and smoking on school grounds, which results in verbal warnings from the principal. These issues are influenced by Motivation and Self-Efficacy. This study uses an associative approach with saturated sampling, involving 88 civil servant teachers (PNS). Data analysis was conducted using multiple linear regression with SPSS 25, including validity, reliability, normality, linearity, and multicollinearity tests. Hypothesis testing was performed through Simultaneous (F-test) and Partial (t-test) analyses. The results indicate that Motivation and Self-Efficacy significantly and positively affect Normative Commitment, both collectively and individually. This study provides insights into how personal motivation and self-belief strengthen teachers' professional commitment.